Public-private engagement and systems resilience in times of health worker strikes in Ghana: Case study of the CHAG-STATE interaction - Buabeng-Baidoo, Bettina (Department of Public Health and Family Medicine, 2024)
Globally, health worker strikes pose a threat to the fundamental human right to the highest level of health, and the realisation of universal health coverage and the effects have been argued to be worse in low- and middle-income countries (LMICs). During health worker strikes in LMICs, private providers have been identified as crucial to maintaining service continuity. However, poor engagement with the private sector might result in compromising the quality of care received at this time and may accrue financial hardship for the population, especially the poor. Ghana has been the site of numerous public sector, nationwide health worker strikes over the past two decades. During these strikes, the grouping of faith-based health providers, networked mainly by the Christian Health Association of Ghana (CHAG), is thought to play an important role in ensuring the continuation of services. However, no study has yet described or explored private and public sector engagement during health worker strikes and whether these interactions may contribute to health system resilience. This case study described and explored the engagement between CHAG and the Government of Ghana (through its Ministry of Health) during public sector health worker strikes from 2010-2016 and its implications for health system resilience. Following an initial scoping literature study, three strike incidents were chosen as embedded units for further analysis. The initial scoping review was followed by a desk-based review of additional data from peer-reviewed literature, institutional databases, and media archives. A secondary analysis of interview transcripts from a related project was also undertaken, and expert consultations were undertaken. Data was analysed using a qualitative thematic approach. Our findings showed that health worker strikes in Ghana were a chronic stressor. We found evidence of system-level interactions between CHAG and the government, where the government publicly directed patients to CHAG facilities to allow for 'absorptive' and 'adaptive' resilience strategies. This was possible due to CHAG's non-striking convention, the two actors' unique secondment policy, and the presence of a National Health Insurance System. We discovered that system 'software' components, including trust, shared values, and power influenced the dynamics of this interaction. However, there was limited evidence of additional support from the government to CHAG facilities during strikes or increased collaboration between the two actors. Additionally, it was found that chronic delays in reimbursements from the National Health Insurance System to private providers may impede the ability of CHAG to provide care and that there were challenges to CHAG's non-striking convention from within and outside the organisation. The study highlights the critical role that private providers can play in enhancing the resilience of the health system during strikes in Ghana. To this end, the government should establish close and proactive partnerships with private providers to guarantee adequate support during such disruptions- including responding to challenges with the National Health Insurance System and scaling up resources at private facilities during strikes. The study also showed that important complexities (including challenges to CHAG's non-striking convention) need to be considered moving forward. Additionally, the government should (with a keen awareness of the complex adaptive nature of health systems) engage in joint efforts with relevant stakeholders to proactively address human resource-related challenges. The case study highlights the continued and expanding significance of private providers (in particular non-profit providers) in the strengthening and resilience of mixed health systems. The study showed the need for further research on the impact of strikes on health systems in LMICs and the strategies (including collaboration with the private sector) that nations can implement to respond effectively. LMICS must plan for strikes by fostering collaborative relationships with the private sector and developing strike preparedness strategies and policies to ensure the continuation of emergency and essential services during these times.